Hormonal-metabolic markers and their relationships in patients with coronary heart disease after suffering from the COVID-19 coronavirus disease - S. M. Manuilov; N. S. Mykhailovska (Patologìâ)
The aim of the study. To investigate the peculiarities of changes in hormonal and metabolic markers and their relationships with neurovegetative disorders in patients with coronary artery disease after suffering from the COVID-19 coronavirus disease (in the long-COVID period).